Faktor-faktor yang Mempengaruhi Penyerapan Hukum Islam dalam Perundang-Undangan Pada Era Orde Baru (1965 s/d 1998) - Jurna Petri Roszi (Institut Agama Islam Negeri (IAIN) Curup, 2017)
The Soeharto government became an interesting theme for nearly every research because of uniqueness of the rule known as the authoritarian nature. However, the uniqueness is only studied until the result of the authoritarian who has raised the anxiety of almost all the people and eventually led to the cessation of Soeharto as head of the State Indonesia. Judging from the perspective of law, the political transition of the period not only political influence, but also influenced the formation of law. This research will discuss about factors influencing absorption of Islamic Law into legislation. In the Order Baru era efforts to ground Islamic law into legislation experienced a variety of responses, both from among Muslims and non-Muslims. Factors affecting the absorption of Islamic law in Indonesia can not be separated from the perennial struggles and tensions in positioning religious relations (shari'a) and the state, between the secularization project and the Islamization of the state and society. This tension occurs in two different important settings. First, the level of scholastic or theoretical-idealistic. Second, the realistic-politic or ideological-empirical level. The debate within the ideological framework has implications for the legal sphere debate. The same complexity is also encountered in internal Muslims because the meaning of sharia itself has its own problems. Where the mazhab of thought and Islamic legal system is not single. The findings of this research is the development of Islamic law in the Order Baru era seen from the legal products that serve as case studies in this study such as UU no. 1 year 1974 about Marriage born at the time of Indonesian political configuration is in otteriter political configuration, but the character of Islamic law product that produced is responsive. Likewise law products UU no. 7 of 1989 on Religious Courts, from the perspective of the formation of a law of responsive character because it is accommodative to Religious Courts institution which is an important part in institutional Islamic law in Indonesia, although UU no. 7 Year 1989 was born when the authoritarian political configuration and in terms of implementation of legal material is conservative. This is seen from the low attention of the political elite to realize the UUPA and even the existence of the institution has existed long before the formal law. In addition, the birth of UUPA is late compared to other judicial laws. Furthermore, the same thing happened to the Compilation of Islamic Law, the Order Baru government's configuration is still considered undemocratic. But in terms of content fully contains the provisions raised from the books of Islamic jurisprudence fiqh containing aspects of marriage, inheritance and perwakafan law. Keywords: Islamic Law, Order Baru, Legislation